Study on a Christian Chinese sample: sense of self-worth, well-being and locus of control - Wu, Fei (Mental health, religion & culture, 2017)
The purpose of this study was to explore Chinese Christians’ sense of self-worth, well-being, locus of control and the correlations between these variables. One hundred and two Chinese Christians with a range of 18-40 years old were surveyed by the Scale of Self-worth, Chinese version of General Well-Being Scale and internal-external Locus of Control Scale. A control group of 134 Chinese non-Christians participated in the same survey. Christians scored lower on locus of control and higher on self-worth than the non-Christians. No significant general well-being difference was between the Christian and non-Christian samples. The correlations were significant between locus of control and self-worth/general well-being (negative) and between self-worth and general well-being (positive). Results suggest that Christians experience better self-worth and tend to be internals on locus of control.